Influence of Stakeholders on Policy Formation in the SME Sector - SULEIMENOVA, Gulimzhan; NURMAGANBETOV, Arman; SHAKEYEV, Sayan; ZHAKSYBAYEV, Kuat; NURSULTAN, Duman (Journal of Advanced Research in Law and Economics; Vol 8 No 6 (2017): JARLE Volume VIII Issue 6(28) Fall 2017, 2017)
The great attention in the world is paid to development of small and medium entrepreneurship sector in Kazakhstan because small and medium business is the main driver of economic growth, elimination of unemployment and increase of social and economic stability in the country. Results of the research allowed to determine the list of stakeholders who are the most influential and important elements while entrepreneurship development policy forming, and also the lists of the stakeholders of less influence, but of considerable importance and vice versa. The SME sector stakeholder analysis made during writing of this work is directed to improvement of understanding of stakeholders' structure and correlations between them, through the determination of stakeholders who play the central and minor roles. The research results will allow organizing more effectively the interaction between stakeholders in successful policy of the SME sector forming.